Plano de prevenção para controle e eliminação de riscos ocupacionais de catadores de materiais recicláveis - Soares, Edson Silva (2019)
Large-scale solid waste generation has led to a scenario of environmental crisis and damage to human health. One of the alternatives mentioned in the literature includes selective collection and the transfer of dry recyclable solid waste to recyclable waste pickers who work on unhealthy conditions and are exposed to various occupational hazards. The main objective of this study was to evaluate the implementation of an Environmental Risk Prevention Plan (PPRA) for the control and elimination of occupational risks in the context of an association of collectors of recyclable materials, through a participatory research that was divided into three stages : recognition of environmental risks; formation of an Internal Commission for the Prevention of Accidents and construction of an Environmental Risk Prevention Plan. The data were collected through direct observation of the activities of recyclable material collectors, photographic records and matrix application. Four workshops were held to raise awareness among the participants about the formation of a CIPA and the importance of the PPRA. Semi-structured interviews were applied before (pre-test) and after the workshops (post-test) to identify if there was a change in the perception of those involved. Subsequently, an Environmental Risk Prevention Plan was prepared which suggested the measures that should be adopted to mitigate environmental risks, taking into account the needs of recyclable materials collectors and their reality. Recyclable waste collectors have been exposed to a variety of physical, chemical, biological, ergonomic and accident hazards through exposure to solar radiation, noise, contact with organic solid waste, sanitary and health services, electrical and electronic components, sharp materials, chemicals, weight lifting and transport, and inadequate postures that may compromise the work capacity, health, and safety of these workers. For mitigation and / or elimination of these risks it is necessary to implement preventive measures and safety standards that favor the control and mitigation of occupational risks through the PPRA and the collaboration of the population, public managers, universities and other spheres of society. The formation process provided several positive impacts, among them: awareness of the risks of the process of collecting recyclable materials, the need for changes in working conditions and attitudes that can lead to accidents, and the implementation of CIPA. In view of the reality of the situation, it was possible to confirm that the creation of an Environmental Risk Prevention Plan (PPRA) could favor the reduction of risks in the process of collecting recyclable materials, even in the face of the social and economic challenges of the profession. The existing technologies in the association partially meet the requirements of current safety standards, since the aspects related to lifting and transporting weight, postures and repetitive movements still do not promote comfort, safety and efficient performance of activities.